REVEALING THE EXISTENCE OF MONEYLENDERS IN TRADING ACTIVITIES AT PARUNG MARKET BASED ON ISLAMIC ECONOMIC PRINCIPLES - Ahmad Maulidizen; Heristina Fitri Rukmana; Muhammad Rafi Thoriq (Jurnal Ekonomi, 2022)
Moneylenders are likened to needs sought by traders in Parung Market as a last resort to provide capital loans. On the other hand, they are equated with moneylenders who are detrimental to traders as service users. However, on the moneylender side, it harms traders by charging high interest, which makes it a burden for traders because they have to share profits with moneylenders. This study focuses on the existence of moneylenders in trading activities at Pasar Parung and analyzes it with an Islamic economic approach. This qualitative research uses interviews, observation, and documentation data collection methods. The research results show that loan sharks at Parung Market have been going on for five years since 2013. The need for capital and the absence of a financial institution is why it exists. The mechanism for accounts receivable by loan sharks is straightforward. Applying for a loan is simple, going through a lengthy procedure. Debt repayments are made in daily instalments for four months / 120 days, with the number of instalments equal to the total loan plus 20% interest divided by 120 days. The mechanism of debt and credit carried out by moneylenders in Islam is included in usury nasi'ah. The practice of loan sharks at Parung Market violates the principles of justice, the principles of ta'awun, and the principles of mashlahah. Moneylenders practice assisting traders in meeting their material needs. However, the spiritual needs of traders are not satisfied, so the income earned does not receive the blessings of Allah